Conservation agriculture for rice-based intensive cropping by smallholders in the Eastern Gangetic Plain - Bell, Richard W.; Haque, Md. Enamul; Jahiruddin, M.; Rahman, Md. Moshiur; Begum, Mahfuza; Miah, M. A. Monayem; Islam, Md. Ariful; Hossen, Md. Anwar; Salahin, Nazmus; Zahan, Taslima; Hossain, Mohammad Mobarak; Alam, Md. Khairul; et al. (MDPI, 2018)
We review the recent development of Conservation Agriculture (CA) for rice-based smallholder farms in the Eastern Gangetic Plain (EGP) and the underpinning research on agronomy, weed control, soil properties and greenhouse gas emissions being tested to accelerate its adoption in Bangladesh. The studies are based mostly on minimum soil disturbance planting in strip planting (SP) mode, using the Versatile Multi-crop Planter (VMP), powered by a two-wheel tractor (2WT). One-pass SP with the VMP decreased fuel costs for crop establishment by up to 85% and labour requirements by up to 50%. We developed strip-based non-puddled rice (Oryza sativa) transplanting (NPT) in minimally-disturbed soil and found that rice grain yield increased (by up to 12%) in longer-term practice of CA. On farms, 75% of NPT crops increased gross margin. For non-rice crops, relative yield increases ranged from 28% for lentil (Lens culinaris) to 6% for wheat (Triticum aestivum) on farms that adopted CA planting. Equivalent profit increases were from 47% for lentil to 560% for mustard (Brassica juncea). Moreover, VMP and CA adopting farms saved 34% of labour costs and lowered total cost by up to 10% for production of lentil, mustard, maize (Zea mays) and wheat. Effective weed control was obtained from the use of a range of pre-emergent and post-emergence herbicides and retention of increased crop residue. In summary, a substantial body of research has demonstrated the benefits of CA and mechanized planting for cost savings, yield increases in many cases, increased profit in most cases and substantial labour saving. Improvement in soil quality has been demonstrated in long-term experiments together with reduced greenhouse gas emissions.